Evaluation of the Relationship of Glasdegib Exposure and Safety End Points in Patients With Refractory Solid Tumors and Hematologic Malignancies. (24th September 2020) - Ruiz‐Garcia, Ana; Shaik, Naveed; Lin, Swan; Jamieson, Catriona; Heuser, Michael; Chan, Geoffrey
Abstract: Glasdegib is approved for treating acute myeloid leukemia in elderly patients at 100 mg once daily in combination with low‐dose cytarabine. Exposure‐efficacy analysis showed that the survival benefit of glasdegib was not glasdegib exposure‐dependent. The relationship between glasdegib exposure and adverse event (AE) cluster terms of clinical concern was explored in this analysis. The incidence and severity of dysgeusia, muscle spasms, renal toxicity, and QT interval prolonged was modeled using ordinal logistic regression. AEs were graded using the National Cancer Institute Common Terminology Criteria for Adverse Events (version 4.03). Estimated pharmacokinetic parameters were used to derive glasdegib exposure metrics. Demographic characteristics, disease factors, and other variables of interest as potential moderators of safety signals were evaluated. Clinical trial data from patients who received single‐agent glasdegib (N = 70; 5–640 mg once daily); or glasdegib (N = 202, 100–200 mg once daily) with low‐dose cytarabine, decitabine, or daunorubicin and cytarabine were analyzed. Glasdegib exposure was statistically significantly associated with the cluster term safety end points dysgeusia, muscle spasms, renal toxicity, and QT interval prolonged . The impact of age on muscle spasms and baseline body weight and creatinine clearance on renal toxicity helped explain the AE grade distribution. At the 100 mg once daily clinical dose, the predicted probabilities of the highest AE grade were 11.3%, 6.7%, 7.7%, and 2.5% for dysgeusia, muscle spasms, renal toxicity, and QT interval prolonged, respectively. Overall, the predicted probability of developing an AE of any severity for these safety end points was low. Therefore, no starting dose adjustments are recommended for glasdegib based on the observed safety profile.